Development of Offshore Finance in Singapore and The Reference to The Construction of Hainan Free Trade Port - Wang, Ruizi (Transactions on Economics, Business and Management Research, 2024)
Singapore, renowned as an offshore financial center, boasts a well-developed financial system and extensive developmental expertise, offering substantial insights for the establishment of the Hainan Free Trade Port. This article presents the three stages of the development of offshore finance in Singapore, and explores the development process of Singapore’s offshore finance, mainly focusing on its fund hedging practices and financial regulation experiences. The aim is to present valuable guidance and perspectives for shaping the financial framework of the Hainan Free Trade Port. Through detailed examination and leveraging lessons from Singapore’s offshore finance, significant reference points have been identified for the development of the Hainan Free Trade Port. These include promotion of financial system, advocacy for preferential tax rates, enhancement of the Renminbi (RMB) Ecosystem and advancement legal foundation and innovation. These initiatives are poised to enhance the economic vitality and global competitiveness of the Hainan Free Trade Port, facilitating the seamless progress towards establishing a world-class Free Trade Port in Hainan.